1998
DOI: 10.1146/annurev.arplant.49.1.585
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding Lignin Biosynthesis

Abstract: After a long period of little change, the basic concepts of lignin biosynthesis have been challenged by new results from genetic modification of lignin content and composition. New techniques for making directed genetic changes in plants, as well as improvements in the analytical techniques used to determine lignin content and composition in plant cell walls, have been used in experimental tests of the accepted lignin biosynthetic pathway. The lignins obtained from genetically modified plants have shown unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
262
1
16

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(287 citation statements)
references
References 90 publications
8
262
1
16
Order By: Relevance
“…Most of the transgenic works have been done in tobacco plants because of the easiness of transformation and the presence of significant amount of second- ary xylem in stems. These studies have demonstrated that not only the lignin content but also the lignin composition can be altered in transgenic plants (Whetten et al, 1998). It has also been shown that alteration of lignin content or composition in transgenic plants could present benefits to reduce pollutions from pulping or increase digestibility of forages (Baucher et al, 1996(Baucher et al, , 1999).…”
Section: Ccoaomt Is An Ideal Target For Genetic Manipulation Of Lignimentioning
confidence: 99%
“…Most of the transgenic works have been done in tobacco plants because of the easiness of transformation and the presence of significant amount of second- ary xylem in stems. These studies have demonstrated that not only the lignin content but also the lignin composition can be altered in transgenic plants (Whetten et al, 1998). It has also been shown that alteration of lignin content or composition in transgenic plants could present benefits to reduce pollutions from pulping or increase digestibility of forages (Baucher et al, 1996(Baucher et al, , 1999).…”
Section: Ccoaomt Is An Ideal Target For Genetic Manipulation Of Lignimentioning
confidence: 99%
“…After synthesis and transport to the cell wall these monomers undergo polymerization via an oxidative coupling mechanism. Recent progress in understanding lignin biosynthesis has been reviewed by Baucher et al (1998) and Whetten et al (1998).…”
Section: Introductionmentioning
confidence: 99%
“…4-Coumarate:coenzyme A (CoA) ligase (4CL) mediates activation of hydroxycinnamic acids 4-(p)-coumaric acid (PA), caffeic acid (CA), ferulic acid (FA), 5-hydroxyferulic acid (5HFA), and sinapic acid (SA) into the high-energy intermediates used for biosynthesis of lignin, flavonoids, and various other protective, attractant, and signaling metabolites (Hahlbrock and Scheel, 1989;Dixon and Paiva, 1995;Higuchi, 1997;Whetten et al, 1998). Multiple 4CL isoforms with differential in vitro substrate specificities have been reported in several species (Knobloch and Hahlbrock, 1975;Ehlting et al, 1999), including aspen (Populus tremuloides Michx.…”
mentioning
confidence: 99%